Compacted Feed Potency to Minimize Cattle Feed Adaptation Period on The New Introduced Feed - Despal Despal; Fensa Eka Widjaya; Yuli Retnani; Rudi Priyanto; Luki Abdullah (Institut Pertanian Bogor, 2022)
Compacted feed such as wafers and pellets is still rarely given to cattle shipping in Indonesia because it requires an adaptation period to the newly introduced feed. This study aimed to observe forage compacted feed potency to minimize the adaptation period of kupang cattle to a new feed with high nutrient content. Two experiments were carried out to observe six feed formulations and four different feed forms. The first experiment was an experiment to determine three of six formulations with the same nutritional content to be tested in the second experiment. The second experiment was to observe four feed forms (wafers, pellets, dry pellets, and cubes) combined with the three best formulations from the first experiment. Six treatments and five replications using 30 cattle and 30 kg of feed were carried out in the first study, while the second one used a randomized factorial design of 4´3 treatments and 5 replications consisting of 60 cattle and 420 kg of feed. The results showed that there was no significant difference between the formulations at the same nutritional level. The highest consumption results were found in the form of wafer followed by cubes, pellets, and dry pellets (P <5%). The conclusion of this study is that the compacted feed in the form of wafers, pellets, and cubes can be used to eliminate the feed adaptation period. Keywords: feed logistics, compacted feed, kupang cattle, adapting period, feed adaptability